Ethnobotany, phytochemistry, and pharmacology of Fritillaria cirrhosa D. Don: A bibliometric analysis of an alpine medicinal herb - Rai, Meera; Tripathi, Vishal; Semwal, Prabhakar; Pant, Gaurav (Ethnobotany Research and Applications, 2026)
Background: Fritillaria cirrhosa D. Don is a high-value alpine medicinal herb endemic to the Himalayan region, valued in traditional Asian medicine for its antioxidant, anti-inflammatory, and respiratory benefits. Its bulbs command high market prices, leading to unsustainable harvesting, ecological threats, and endangered status (IUCN Vulnerable). Despite its ethnobotanical, phytochemical, and pharmacological significance, research trends and gaps remain underexplored, necessitating a bibliometric analysis to map scientific output, collaborations, and future directions for conservation and sustainable use. Methods: This bibliometric study analyzed publications on F. cirrhosa from 1939 to June 2025, retrieved from the SCOPUS database using search strings targeting "Fritillaria cirrhosa" and synonyms like "Fritillaria roylei." Data were processed with VOSviewer for network visualization (co-authorship, co-occurrence) and R Studio (Bibliometrix) for trends, citations, and thematic mapping. Results: A total of 128 documents were analyzed, revealing China’s dominance (89 documents, 1538 citations), followed by India (24 documents, 250 citations) and Hong Kong (17 documents, 368 citations). Top institutions included Sichuan University (53 articles) and Chengdu University (51 articles), with key authors like Wang S (h-index 7, 266 citations), Li, P (h-index 6, 270 citations). Citation analysis showed recent publications gaining rapid impact, while keyword clusters emphasized traditional medicine, alkaloids, and pharmacology. However, from 2020 onwards, the publication and citation record or research output of the Fritillaria cirrhosa drastically increases, which signifies that the species globally is gaining attention among researchers. Conclusions: This first bibliometric analysis highlights research imbalances, with negligible contributions from other Asian countries like India, Nepal, and Pakistan. Despite the rich species’ distribution in the countries, the publication and citation trends were still restricted. This would largely impact the species’ global attention and scientific evidence at the international level. Keywords: Fritillaria cirrhosa, Medicinal properties, R Studio, Forest product, NTFP, Ethnobotany.